A novel policy gradient algorithm with PSO-based parameter exploration for continuous control. (April 2020) - Liu, Tundong; Li, Liduan; Shao, Guifang; Wu, Xiaomin; Huang, Meng
Abstract: Continuous control has attracted enormous attention due to its essential role in real-world applications. However, it is considerably difficult to be addressed through explicitly modeling in practice. As promising approaches, model-free policy gradient (PG) based methods in reinforcement learning (RL), however, suffer from slow convergence and complex computation owing to the high variance of gradient estimating and sophisticated backpropagation. Therefore, in this paper, a gradient-free policy gradient algorithm with PSO-based parameter exploration (PG-PSOPE) is proposed for continuous control tasks. To reduce variance and improve convergence rate, the PSO is combined with PG to provide a novel way for training policy network in RL. Experimental results of simulated physical control tasks verify the effectiveness of the proposed algorithm. Besides, the PG-PSOPE is superior in both convergence speed and final performance to the typical on-policy PG and the off-policy deep RL method. Furthermore, the PG-PSOPE exhibits the simplicity and high effectiveness by comparison of training time under different tasks, and its running time is reduced by 58 times compared with other gradient-based methods for the best case.